New therapeutic approach for tricuspid regurgitation: Transcatheter tricuspid valve replacement or repair - Blusztein, David I.; Hahn, Rebecca T. (Frontiers in Cardiovascular Medicine, 2023)
The tricuspid valve is a complex structure with normal function dependent on the leaflet morphology, right atrial and annular dynamics, and right ventricular and chordal support. Thus, the pathophysiology of tricuspid regurgitation (TR) is equally complex and current medical and surgical management options are limited. Transcatheter devices are currently being investigated as possible treatment options with lower morbidity and mortality than open surgical procedures. These devices can be divided by their implant location/mechanism of action: leaflet approximation devices, annuloplasty devices, orthotopic valve implants, and heterotopic valve implants. The current review will discuss each class of transcatheter device therapy, and further delve into the current understanding of who and when to treat. Finally, we will include a brief discussion of the future of device and surgical therapy trials for TR and the remaining questions to answer about this complex disease process.